2013
DOI: 10.1002/cncr.28161
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting patients into the CDC's Colorectal Cancer Screening Demonstration Program

Abstract: BACKGROUND In 2005, the Centers for Disease Control and Prevention (CDC) funded 5 sites as part of the Colorectal Cancer Screening Demonstration Program (CRCSDP) to provide colorectal cancer screening to low-income, uninsured, and underinsured individuals. Funded sites experienced unexpected challenges in recruiting patients for services. METHODS The authors conducted a longitudinal, qualitative case study of all 5 sites to document program implementation, including recruitment. Data were collected during 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 41 publications
(107 reference statements)
0
46
0
Order By: Relevance
“…Uninsured, low‐income populations were the primary target of the program. Descriptions and evaluations of the CDC demonstration program were published in 2013 . DeGroff et al identified facilitating and challenging factors for the initiation and launch of this program through interviews and document review .…”
Section: Review Of Model Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uninsured, low‐income populations were the primary target of the program. Descriptions and evaluations of the CDC demonstration program were published in 2013 . DeGroff et al identified facilitating and challenging factors for the initiation and launch of this program through interviews and document review .…”
Section: Review Of Model Programsmentioning
confidence: 99%
“…Three sites (St. Louis, Nebraska, and Seattle) initially chose guaiac fecal occult blood testing (gFOBT) as the screening test of choice (with follow‐up CS for any positive result); the remaining sites (Baltimore and Suffolk County) chose CS as the primary screening method. The 5 sites drew on existing delivery systems, especially those that already were organized to deliver services supported by the CDC‐funded National Breast and Cervical Cancer Early Detection Program . An example of this is using a shared outreach or in‐reach system or tailoring program components to be integrated into clinical structures that were already in place.…”
Section: Review Of Model Programsmentioning
confidence: 99%
“…Funds were provided to support both clinical (screening, surveillance, and diagnostic services) and associated services (office visits and patient navigation) activities for patients aged ≥50 years. These activities are described elsewhere in this supplement to Cancer . The local programs contracted with a variety of providers and health care systems, including primary care providers (PCPs), gastroenterologists, surgeons, pathologists, gastroenterology centers, laboratories, hospitals, and community health clinics, to create provider networks required for CRC screening .…”
Section: Introductionmentioning
confidence: 99%
“…The sites in Baltimore City and Suffolk County, New York used colonoscopy as their primary screening test throughout the demonstration. Each site has been described in detail in previous articles, and each is also described elsewhere in this supplement to Cancer …”
Section: Introductionmentioning
confidence: 99%
“…From 2005 to 2009, the Centers for Disease Control and Prevention (CDC) established and supported a 4‐year Colorectal Cancer Screening Demonstration Program (CRCSDP) for low‐income, under‐ or uninsured men and women 50‐64 years of age living in the United States at or below 250%‐350% of the federal poverty level . Five sites received funding for this initiative: 1) the Maryland Department of Health and Mental Hygiene (referred to as the Baltimore city site), 2) the Missouri Department of Health and Senior Services (referred to as the St. Louis site), 3) the Nebraska Department of Health and Human Services (referred to as the Nebraska site), 4) Public Health—Seattle & King County (referred to as the greater Seattle site), and 5) the Stony Brook University Medical Center (referred to as the Suffolk County, New York, site).…”
Section: Summary Of Crcsdp Findingsmentioning
confidence: 99%